Interactive Effects of Agrivoltaic Shading, Irrigation, and Biofertilizers on the Chemical Composition of Lettuce Leaves (Lactuca sativa L.): Pengaruh Interaktif Peneduh Agrivoltaic, Irigasi, dan Pupuk Hayati terhadap Komposisi Kimia Daun Selada (Lactuca sativa L.) - Khudhair, Manar Ali; Sahib, Mohammed R.; AL-Agele , Hadi A. (Universitas Muhammadiyah Sidoarjo, 2024)
The agrivoltaic system is one of the most efficient approaches to sustainability, optimizing agricultural land for simultaneous food production and electricity generation. This technique decreases water usage by providing shade to soil and vegetation, therefore reducing evaporation and prolonging soil moisture retention relative to open-field farming. This study sought to examine the impact of shaded versus unshaded cultivation, irrigation levels (100% and 50%), and biofertilizer application on the concentration of chemical characteristics in plant leaves. The findings demonstrated that both shaded and unshaded cultivation markedly enhanced leaf concentrations of chlorophyll, and carbohydrates. Biofertilizer, consisting of a mixture of Trichoderma and mycorrhiza, markedly improved chlorophyll and carbohydrates levels in leaves. Nonetheless, irrigation levels exhibited no substantial impact on the leaf concentrations of flavonoids, nitrates, or carbs. The combination of shaded cultivation with biofertilizer led to substantial enhancements in chlorophyll, flavonoids, carbs, and nitrate levels. The combination of shaded cultivation and irrigation markedly increased the levels of chlorophyll, flavonoids, nitrates, and carbohydrates. Furthermore, the interaction between irrigation and biofertilizer demonstrated notable enhancements in chlorophyll and nitrate levels. Ultimately, the triple combination of shade, irrigation, and biofertilizer significantly influenced all examined parameters, resulting in elevated levels of chlorophyll, flavonoids, nitrates, and carbohydrates in leaf tissues. Highlights: Agrivoltaics optimize land, reducing evaporation and boosting soil moisture retention. Shade and biofertilizer enhance chlorophyll, flavonoids, carbohydrates, and nitrate levels. Combined shade, irrigation, and biofertilizer significantly improve all leaf chemical parameters.. Keywords: Agrivoltaic system, bio-fertilization, drip irrigation, deficit irrigation, chemical traits